An Exploration of Mutagenesis in a Family with Cleidocranial Dysplasia without RUNX2 Mutation - Liu, Dandan; Liu, Yang; Zhang, XianLi; Wang, Yixiang; Zhang, Chenying; Zheng, Shuguo (Frontiers in Genetics, 2021)
Cleidocranial dysplasia (CCD) is an autosomal dominant inheritable skeletal disorder characterized by cranial dysplasia, clavicle hypoplasia, and dental abnormalities. Mutations involving RUNX2 have been the only known molecular etiology for CCD but not identified in all CCD patients. Any abnormality of RUNX2 couldn't be detected in about 20% - 30% of patients, and the molecular cause remained unknown. In the present study, a family case with typical features of CCD was included. RUNX2 mutation was first screened by sequencing analysis, and no mutation was detected. Copy number alterations of the RUNX2 gene were then measured by quantitative PCR and Multiplex ligation-dependent probe amplification (MLPA). Similarly, any copy number variation in RUNX2 had not been detected either. We performed whole-exome sequencing (WES) to identify the underlying genetic mutations. Beyond expectations, any abnormality had not been detected in genes known to be related to the RUNX2 signaling pathway. Therefore, it was supposed that other new unknown gene variations might contribute to the CCD patients. IGSF10 had been focused, a gene that was related to bone development. An IGSF10 frameshift mutation (c.6001_6002delCT, p.Leu2001Valfs*24) was detected by WES. Sanger sequencing verified that this mutation was only detected in the patient and her affected mother but not in other unaffected family members. Bioinformatics studies demonstrated that the detected mutation could change the 3D structure of the IGSF10 protein and severely damaged the function of IGSF10. In addition, ALP activity and ability to form mineralized nodules were interfered with by IGSF10 knockdown compared to normal control. The expression of BSP was significantly reduced by IGSF10 knockdown, but not for other osteogenic markers. Our results provide new genetic evidence that mutation involved in IGSF10 might contribute to CCD.